Integration of digital technologies in Mathematics teaching and learning: the role of teacher training - Carvalho, Renata (Aprender, 2023)
The integration of digital technologies in mathematics teaching and learning is a continuous but necessary challenge that teacher training should support. This article reports a teacher training experience with elementary school teachers (grades 1 to 6), which is believed to have facilitated the integration of digital resources in the mathematics classroom to explore mathematical concepts. To support the integration of digital resources in the mathematics classroom, and to develop teachers' pedagogical, technological, and mathematical content knowledge, a 20-hour training course was planned and carried out between 2020 and 2022, counting with several editions in which about 130 teachers participated. In their reflection about the training process, teachers recognize the importance of the dynamics, tasks, and resources used in the training and value the way they were involved and challenged to explore, reflect, discuss, and plan tasks with digital resources for the mathematics classroom. This involvement broke down barriers, overcame constraints in using technologies, and motivated teachers to experiment digital resources with their students.
Keywords: teacher training; mathematics teaching and learning; digital technologies